2017
DOI: 10.1002/srin.201700157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Welding Heat Input on Microstructure and Toughness of Heated‐Affected Zone in Steel Plate with Mg Deoxidation

Abstract: Effect of heat input on the microstructure and toughness of heat-affected zone (HAZ) in steel plate with Mg deoxidation has been investigated through welding thermal cycle simulation method. With the heat input increasing from 100-400 kJ cm À1 , the average prior-austenite grain (PAG) size is increased from 43 to 56 and then to 173 mm, and the HAZ microstructure is changed from fine bainite lath to relative larger bainite lath and then to grain boundary ferrite (GBF) and intragranular acicular ferrite (IAF). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…It was observed that the major kind of inclusions in Al-killed steel was the Al 2 O 3 -MnS inclusion, which was unable to nucleate an acicular ferrite during the high-heat-input welding process [10,11]. According to reports in recent literature, in Mg deoxidized steels containing a low level of Al content, Mg-containing inclusions, such as MgO-MnS [12], (Mg-Ti-O)-MnS [7], (Mg-Al-Ti-O)-MnS [11], and (Ti-Ca-Mg-O)-MnS [13], were favorable to promote the formation of IAF, resulting in enhanced HAZ toughness. However, the effect of inclusions formed in Mg deoxidized steel containing a high level of Al content on the HAZ microstructure and toughness has not yet been understood comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the major kind of inclusions in Al-killed steel was the Al 2 O 3 -MnS inclusion, which was unable to nucleate an acicular ferrite during the high-heat-input welding process [10,11]. According to reports in recent literature, in Mg deoxidized steels containing a low level of Al content, Mg-containing inclusions, such as MgO-MnS [12], (Mg-Ti-O)-MnS [7], (Mg-Al-Ti-O)-MnS [11], and (Ti-Ca-Mg-O)-MnS [13], were favorable to promote the formation of IAF, resulting in enhanced HAZ toughness. However, the effect of inclusions formed in Mg deoxidized steel containing a high level of Al content on the HAZ microstructure and toughness has not yet been understood comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Xu et al reported that Mg addition to a shipbuilding steel can significantly induce the formation of the interlocking intragranular acicular ferrite (IAF), which has an excellent strength-toughness combination. [7,8] Wang et al highlighted the positive effect of Ti-Zr deoxidation in a low-alloy steel, revealing great improvement in intragranular transformation and strong prevention of coarse intergranular structures. [9] Yamamoto et al summarized the formation mechanism of IAF in HSLA steels noting that MnS forms a Mn-depleted zone at the Ti 2 O 3 /austenite interface, thus increasing the chemical free energy change for ferrite nucleation, and TiN decreases the interfacial energy for ferrite nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] During the HHIW process, the microstructures in the coarse‐grained heat‐affected zone (CGHAZ) are coarsened, giving rise to the deterioration of the HAZ toughness. [ 2,3 ] Therefore, it is of considerable importance to improve their HAZ toughness after HHIW.…”
Section: Introductionmentioning
confidence: 99%